LITERATURE REVIEW : THE IMPACT OF CORRUPTION ON ECONOMIC GROWTH A CASE STUDY BY COUNTRY: SAUDI ARABIA, QATAR AND TURKIYE - Susilo, Joko (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2024)
This study examines the direct influence of corruption on economic development in Saudi Arabia, Qatar, and Turkiye. The descriptive analysis is offered in tables and narratives related to the results obtained from the articles collected in the form of a literature review. The findings of this literature study indicate that researchers have identified a detrimental influence of corruption on economic growth. Specifically, corruption has been seen to have direct repercussions on variables such as the debt-to-GDP ratio and Foreign Direct Investment, posing a substantial obstacle to sustainable development. On the other hand, corruption has indirect consequences via many transmission channels, such as its impact on investments in physical capital. This study aims to conduct a comprehensive literature analysis using a comparative case study approach focusing on three countries: Saudi Arabia, Qatar, and Turkiye. In contrast, scholars like the Organization of Islamic Cooperation (OIC), GCC Countries, and D-8 Countries want to undertake targeted investigations. To the author's understanding, this study represents a pioneering effort to establish an empirical and theoretical foundation to support the researcher's analysis of the ramifications of corruption within Saudi Arabia, Qatar, and Turkiye.